Gait Speed Is Not Associated with Vasogenic Shock or Cardiogenic Shock following Cardiac Surgery, but Is Associated with Increased Hospital Length of Stay. (23rd October 2018) - Clark, Kimmie; Leathers, Taylor; Rotich, Duncan; He, Jianghua; Wirtz, Katy; Daon, Emmanuel; Flynn, Brigid C.
Abstract : Objective . Frailty has been associated with adverse outcomes following cardiac surgery. Gait speed has been validated as a marker of frailty. Slow gait speed has been found to be associated with mortality after cardiac surgery. However, it is unknown why slow gait speed predisposes to cardiac surgical mortality. Design . A retrospective analysis. Participants. Patients undergoing cardiac surgery who had a 5-meter walk test performed preoperatively (n = 333 of 1735 total surgical patients) from January 2013 to March 2017. Setting . A tertiary care academic hospital. Measurements and main results. Gait speeds were stratified by tertiles: <0.83 m/s, 0.83–1 m/s, and >1 m/s. There was no difference in the incidence of cardiogenic or vasogenic shock when comparing the gait speed groups. Total hospital length of stay was significantly different among the gait speed groups (p = 0.0050 ). Also, patients in the slowest gait speed tertile had a significant association with need for a postoperative permanent pacemaker (p = 0.0298 ). Conclusion . There was no significant association between gait speed and the incidence of cardiogenic or vasogenic shock after cardiac surgery. Gait speed was associated with increased hospital length of stay and need for a permanent pacemaker after cardiac surgery.